A defective flexible loop contributes to the processing and gating defects of the predominant cystic fibrosis‐causing mutation. Issue 4 (22nd January 2019) - Chen, Xinying; Zhu, Siyu; Zhenin, Michael; Xu, Weiyi; Bose, Samuel J.; Wong, Molly Pik‐Fan; Leung, George P. H.; Senderowitz, Hanoch; Chen, Jeng‐Haur
ABSTRACT: People with the genetic disease cystic fibrosis (CF) often carry a deletion mutation ∆F508 on the gene encoding the CF transmembrane conductance regulator (CFTR) Cl − channel. This mutation greatly reduces the CFTR maturation process and slows the channel opening rate. Here, we investigate whether residues near F508 contribute to these defects in ∆F508‐CFTR. Most deletion mutations, but not alanine substitutions, of individual residues from positions 503 to 513 impaired CFTR maturation. Interestingly, only protein processing of ∆Y512‐CFTR, like that of ∆F508‐CFTR, was greatly improved by low‐temperature culture at 27°C or small‐molecule corrector C18. The 2 mutant Cl − channels were equally slow to open, suggesting that they may share common structural flaws. Studies on the H3‐H4 loop that links residues F508 and Y512 demonstrate that G509A/V510G mutations, moving G5091 position backward in the loop, markedly enhanced ∆F508‐CFTR maturation and opening rate while promoting protein stability and persistence of the H3 helix in ∆F508 nucleotide‐binding domain 1. Moreover, V510A/S511A mutations noticeably increased ∆Y512‐CFTR maturation at 27°C and its opening rate. Thus, loop abnormalities may contribute to ∆F508‐ and ∆Y512‐CFTR defects. Importantly, correcting defects from G509 displacement in ∆F508‐CFTR may offer a new avenue for drug discovery and CF treatments.—Chen, X., Zhu, S., Zhenin, M., Xu, W., Bose, S. J., Wong, M. P.‐F., Leung, G. P. H., Senderowitz, H., Chen, J.‐H. A defective flexible loop contributes to the processing and gating defects of the predominant cystic fibrosis‐causing mutation. FASEB J. 33, 5126–5142 (2019). www.fasebj.org